Efficacy and safety of transarterial chemoembolization plus lenvatinib combined with PD-1 inhibitors versus transarterial chemoembolization plus lenvatinib for unresectable hepatocellular carcinoma: a meta-analysis - Chen, Yue; Jia, Luyao; Li, Yu; Cui, Wenhao; Wang, Jukun; Zhang, Chao; Bian, Chunjing; Luo, Tao (Frontiers in Immunology, 2024)
Background Locoregional treatment combined with systemic therapy is expected to play a synergistic anticancer role. We conducted this systemic meta-analysis to examine the efficacy and safety of transarterial chemoembolization (TACE) plus lenvatinib with or without programmed cell death protein-1 (PD-1) inhibitors (TLP group) compared with TACE + lenvatinib (TL group) for unresectable hepatocellular carcinoma (uHCC). Methods From the inception date to April 2024, the data from PubMed, EMBASE, the Cochrane Library, Ovid, Web of Science, and Clinical Trials. gov were used for meta-analysis. All clinical outcomes of interest included overall survival (OS), progression-free survival (PFS), objective response rate (ORR), disease control rate (DCR), and adverse events (AEs). The hazard ratio (HR) and risk ratio (RR) with 95% confidence intervals (CI) were used to measure the pooled effect. Results This study included 10 retrospective cohort studies, including 1128 patients. The OS (HR=0.51; 95% CI: 0.43–0.60, P < 0.05), PFS (HR=0.52; 95% CI: 0.45–0.61, P < 0.05), ORR (RR = 1.58; 95% CI: 1.37–1.83; P < 0.05) and DCR (RR = 1.31; 95% CI: 1.20–1.43; P < 0.05) were significantly higher in TLP group than in the TL group. The incidence of AEs was acceptable. Prognostic factor analysis identified that ECOG PS (1/0), Child-Pugh class (B/A), BCLC stage (C/B) and main portal vein invasion (yes/no) were independent prognostic factors for OS. BCLC stage (C/B) and main portal vein invasion (yes/no) were independent prognostic factors for PFS. Conclusion The TLP group had better efficacy for uHCC than that of the TL group, with acceptable safety. Systematic review registration PROSPERO, identifier (CRD42023420093).